Combating COVID-19: the India initiatives - Kharb, Preeti; Kapoor, Vinod; Madan, Nishant (International Journal Of Community Medicine And Public Health, 2020)
COVID-19 pandemic is one of the few in the history of mankind and presents an enormous global challenge requiring intervention on unprecedented levels. SARS-CoV-2 is a novel virus spreading exceptionally fast and carries high mortality. Health is an important component for human well-being and economic progress. The healthcare set ups globally are being overwhelmed to treat the serious patients with the needs of medical devices such as ventilators for which there is a global shortage. The COVID-19 pandemic has clearly shown the need for further research, developing new vaccines and treatment for COVID-19. To prevent the disease is the only option countries have at the moment for which nationwide lockdown have been implemented. The Government of India has taken several steps from implementing lockdown, announcing a relief package of Rs. 1.7 lakh crores, and rapid improvement in testing capacity among many others. Government of India is committed to facilitate universal and affordable access to all relevant medical products and technologies, both existing and new, to tackle COVID-19 to accelerate progress towards achieving sustainable development goals and universal health coverage. In this article we present the initiatives taken by government to combat COVID-19 pandemic specifically related to the health products.